Using Reduced Inoculum Densities of Mycobacterium tuberculosis in MGIT Pyrazinamide Susceptibility Testing to Prevent False-Resistant Results and Improve Accuracy: A Multicenter Evaluation. (8th November 2017) - Morlock, Glenn P.; Tyrrell, Frances C.; Baynham, Dorothy; Escuyer, Vincent E.; Green, Nicole; Kim, Youngmi; Longley-Olson, Patricia A.; Parrish, Nicole; Pennington, Courtney; Tan, Desmond; Austin, Brett; Posey, James E.
Abstract : The primary platform used for pyrazinamide (PZA) susceptibility testing of Mycobacterium tuberculosis is the MGIT culture system (Becton Dickinson). Since false-resistant results have been associated with the use of this system, we conducted a multicenter evaluation to determine the effect of using a reduced cell density inoculum on the rate of false resistance. Two reduced inoculum densities were compared with that prescribed by the manufacturer (designated as "BD" method). The reduced inoculum methods (designated as "A" and "C") were identical to the manufacturer's protocol in all aspects with the exception of the cell density of the inoculum. Twenty genetically and phenotypically characterized M. tuberculosis isolates were tested in duplicate by ten independent laboratories using the three inoculum methods. False-resistant results declined from 21.1% using the standard "BD" method to 5.7% using the intermediate ("A") inoculum and further declined to 2.8% using the most dilute ("C") inoculum method. The percentages of the resistant results that were false-resistant declined from 55.2% for the "BD" test to 28.8% and 16.0% for the "A" and "C" tests, respectively. These results represent compelling evidence that the occurrence of false-resistant MGIT PZA susceptibility test results can be mitigated through the use of reduced inoculum densities.